Az egyesülettel összefüggő új polgári jogi szabályozás az alkotmánybírósági határozatok tükrében - Kaprinay, Zsófia (Debreceni Jogi Műhely, 2014)
After the creation of the Basic Law of Hungary, and following a drawn discussion Act CLXXV of 2011 on the Right of Association and the Operation and Funding of Civil Society organizations has come into force (hereinafter referred to as Civil Act). The Civil Act repealed a lot former provitions, thus the Act II. of 1989 on the Right of Association, the law concerning non-profit status, and the provitions related to association of the previous Civil Code. The new Act V of 2013 in the Civil Code has also brought significant changes according to associations.The base of the rules has changed considerabely, as the permissive legislation, and the freedom of the parties has become the main line.At present to association the Civil Act, the new regulations about the court registration of associations – such as Act CLXXXI of 2011 –, and the provisions concerning legal persons and associations of the new Civil Code should be applied.Since the relevant legal regulation has changed, the previous judicial practice is not applicable, courts have to answer the questions among the new legal circumstances as well. However it is sure that the basis of association is the right of association which is a constitutional fundamental right. Due to these significant changes in this paper I have examined those important Constitutional Court Rulings which can be connected with the right of association, and I have tried to compare the decisions of the Constitutional Court with the new present regulation.